Myiasis in maxillofacial region: series of three cases - Cleverson Patussi; Daniela Cristina Lunelli; Regiane Benez Bixofis; Maria Isabela Guebur; José Luiz Dissenha; Laurindo Moacir Sassi (Revista Sul-Brasileira de Odontologia, 2015)
Myiasis is a disease caused by larvae of flies in organs and tissues of man or other vertebrate animals, where they install and evolve as parasites. The human myiasis is common in tropical countries, most frequently affecting rural people, immunocompromised patients and those with psychiatric disorders. It has great destructive potential and needs adequate prevention and treatment for resolution or non-occurrence of this manifestation. Objective: This paper aims to report a series of three cases of patients with presence of myiasis in face: 1) firearm injury postoperative complication in the mandible in a drug user patient; 2) wound after trauma in the region of the upper lip in a patient using illicit drugs; and 3) complication due to poor oral hygiene of a patient with neurological and motor deficits. Case report: The care required by these patients is different because this complication is easily prevented by basic and personal health care, although it represents a complicating factor for surgical procedures and/or dental care. Conclusion: The role of health professionals in patients with special needs and/or drug addiction become sometimes a challenge for dental practice, requiring individualized attention to each patient.